KEPASTIAN HUKUM PENDAFTARAN HAK TANGGUNGAN BERDASARKAN PERATURAN MENTERI AGRARIA DAN TATA RUANG/KEPALA BADAN PERTANAHAN NASIONAL 5 TAHUN 2020 TENTANG PELAYANAN HAK TANGGGUNGAN TERINTEGRASI SECARA ELEKTRONIK - Ni Putu Yunika Sulistyawati,; Sang Ayu Made Ary Kusumardhani; I Komang Indra Witara Murti (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
Mortgage registration is a procedure and requirement that must be passed by the registrant until it is realized by the issuance of a mortgage certificate. The problem of this research is how is the legal certainty of electronic mortgage registration based on the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 5 of 2020 concerning Electronically Integrated Mortgage Services. Electronically Integrated Mortgage Services called the HT-El System is a service process mortgage rights in the context of maintaining land registration data organized through an integrated electronic system. The legal certainty of Electronic Mortgage registration based on the Regulation of the Minister of Agrarian and Spatial Planning / Head of the National Land Agency Number 5 of 2020 concerning Electronic Integrated Mortgage Services guarantees legal certainty for both Mortgage Providers, Mortgage Recipients and third parties. The implementation follows the rules in the implementation of electronic mortgage registration in accordance with the provisions of Article 10 regarding the role of land certificate making officials (PPAT) in the electronic mortgage registration process, for the sake of the integrity and authenticity of electronic documents, the mortgage certificate issued by the electronic mortgage system is marked electronic hand used as a means of verification and authentication. Of course, legal certainty is guaranteed for all parties, both the official for making land deeds (PPAT), and the Agrarian and Spatial Planning Office/National Land Agency.